FRI0094 LONG TERM DRUG SURVIVAL FOR BIOSIMILAR SB4 ETANERCEPT IN RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS AND AXIAL SPONDYLOARTHRITIS PATIENTS WITH A NON-MEDICAL SWITCH FROM ETANERCEPT REFERENCE DRUG. (June 2019) - Haugeberg, Glenn; Fevang, Bjørg Tilde Svanes; Bakland, Gunnstein; Rødevand, Erik; Diamantopoulos, Andreas
Abstract : Background: In the new millennium biologic therapies e.g. tumor necrosis factor inhibitors (TNFi) have played a major role improving clinical outcomes in rheumatoid arthritis (RA), psoriatic arthritis (PsA) and axial spondyloarthritis (ax-SpA). A major limitation in many countries for prescribing these drugs has been the high drug costs. The patent period for several of these TNFis e.g. infliximab, etanercept and adalimumab has ended and as a consequence biosimilar TNFis are now reaching the market. This has a cost saving potential for payers. In Norway, encouraged by the health authorities, non-medical switch from originator to biosimilar has been performed in most patients on biologic originator drugs with biosimilar drugs available, including etanercept. To the best of our knowledge no longer than one year real life experienced real life evidence data for non-medical switch from originator etanercept to biosimilar etanercept SB4 exist (ref.1). Objectives: To explore three-year drug survival for biosimilar SB4-etanercept in RA, PsA and ax-SpA patients with a non-medical switch from etanercept originator to SB4. Methods: At the participating outpatient clinics patients with RA, PsA and ax-SpA are monitored using a clinical computer system, as standard clinical care. Demographic, clinical and treatment data were retrieved from the computer system for patients who started treatment with biosimilar etanercept SB4 between January 2016 and January 2019. Kaplan-Meier survival curves were used to explore drug survival. Survival differences between groups were tested using Breslow statistics. Results: At the participating outpatient clinics since 2016 a total of 474 RA, 249 PsA and 320 ax-SpA patients had a non-medical switch from etanercept originator to biosimilar etanercept SB4. In RA, PsA and ax-SpA patients the percentage of women was 68.2%, 42.6% and 30.3%, the percentage of current smokers 17.0%, 12.8% and 19.6%, mean (SD) age was 63.0 (13.1), 58.2 (11.3), 53.1 (12.1) years and disease duration 16.8 (9.8), 16.1 (9.7), 17.7 (11.0) years, respectively. In RA 80.0% were anti-CCP positive and in PsA and ax-SpA 34.4% and 90.8% were HLAB27 positive. In the table selected disease measures at baseline are shown. No significant difference (p=0.97) in drug survival for SB4 was seen between RA, PsA and ax-SpA patients. Mean (95% CI) SB4 drug survival time (years) was for RA 2.3 (2.2-2.4), for PsA 2.3 (2.2-2.4) and for ax-SpA 2.4 (2.3-2.5). In the figure below Kaplan-Meier drug survival curves are shown. Men had a statistically significant longer mean drug survival than women (2.5 (2.4-2.6) vs 2.2 (2.1-2.3), p=0.001). Conclusion: Our long term real life data show that the majority of patients with a non-medical switch from originator etanercept to biosimilar etanercept SB4 remained on the drug. No significant difference in drug survival was seen between RA, PsA and ax-Spa patients. Men however had a significantly longer drug survival than women. Further analyses are needed to explore reasons for cessation across gender and patient groups. Reference: [1] Glintborg B et al. Ann Rheum Dis 2018;0:1-9 Disclosure of Interests: Glenn Haugeberg Grant/research support from: For this study grant from Biogen, Consultant for: Medical Advisory boards for several companies, Paid instructor for: I have been paid for giving lectures for pharmaceutical companies and their employees, Speakers bureau: I have been paid for giving lectures in meetings organized by pharmaceutical companies, Bjørg Tilde Svanes Fevang: None declared, Gunnstein Bakland: None declared, Erik Rødevand: None declared, Andreas Diamantopoulos: None declared